[OP.LB03.03] THE RELATIONSHIP BETWEEN DIASTOLIC FUNCTION AND CENTRAL HEMODYNAMICS IN DIABETIC HYPERTENSIVE PATIENTS. (September 2016) - Agnoletti, D.; Lieber, A.; Valbusa, F.; Arcaro, G.; Safar, M.E.; Blacher, J.
Abstract : Objective: Diabetic hypertensives patients present different hemodynamic pattern than only hypertensive patients. We aimed to investigate the relationship between the diastolic function and the pulse pressure amplification (PPA), an index combining both arterial stiffness and wave reflexion, in diabetic hypertensives subjects compared to hypertensive subjects. Figure. No caption available. Design and method: We examined 123 patients admitted to the one day hospital of the Hotel-Dieu Hospital (Paris, France) for cardiovascular risk assessment. Anthropometric, laboratory and clinical measurements were collected. Hemodynamic parameters (central blood pressure, aortic pulse wave velocity [PWV], augmentation index [AIx] and PPA) were measured using applanation tonometry. Standard ultrasound echocardiography was performed. Results: Diabetic hypertensive subjects (n = 44) were older than hypertensive subjects (n = 79)(mean age[SD] 64[9] vs 56[14], p < 0.05), and they presented similar cardiovascular risk factors frequencies. Gender was equally distributed. The diastolic function, assessed by the E/E′ ratio was significantly positively correlated with PWV in total population (r = 0.19, p = 0.03), with no differences between the two groups. At the contrary, as shown in the figure, E/E′ ratio was not correlated with PPA in total population, but it was significantly and negatively correlated with PPA only in the diabetic group (p for interaction 0.007, r = - 0.35, p = 0.02). The multiregression analysis (containing all the confounding variables) in this group revealed as significant (p value < 0.05) determinants of PPA: the diastolic function (partial-R 2  = 0.14), gender (partial-R 2  = 0.27), heart rate (partial-R 2  = 0.26), angiotensin blockers treatement (partial-R 2  = 0.13). Conclusions: We confirmed that diabetic hypertensive patients have different hemodynamic behaviour than hypertensive non-diabetic patients. The results suggest that the mechanisms linking diastolic function with PPA are more prominent in diabetic patients.